PENGEMBANGAN INSTRUMEN PENILAIAN BERBASIS SOAL HOTS BERBANTUAN GOOGLE FORM PADA MATA PELAJARAN IPA SISWA KELAS V(LIMA) SDN TULUSREJO 3 MALANG - Fina Arianti; Siti Faizah; Mardhatillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop a HOTS question-based assessment instrument that can be used to assess students' high-level thinking abilities in Class V science subjects at SDN Tulusrejo 3 Malang. This research uses an R&D (Research and Development) approach. This research uses the ADDIE development model which includes five stages, namely Analysis, Design (planning), Development (development), Implementation (implementation), and Evaluation (evaluation). The test subjects in this research were 21 students of class V (five) at SDN Tulusrejo 3 Malang. The types of data used in this research are qualitative and quantitative data. In this research, qualitative data was obtained from observation, interviews and documentation. Meanwhile, quantitative data was obtained from question validation sheets and trial results. The results of this research show that the product validity test results of the HOTS question-based assessment instrument assisted by Google Form obtained an average score of 4.26 with the criteria "Very valid". So, it can be concluded that the development of an assessment instrument based on hot questions with the help of Google Form is valid for use in testing activities with students. Meanwhile, in terms of product testing, an average score of 80.9% (rounded to 81) was obtained, which is included in the "Effective" category. It can be concluded that the development of Hots question-based assessment instruments in science learning assisted by Google Form is effective in improving the evaluation, creativity, analysis and critical thinking skills of fifth grade students at SDN Tulusrejo 3 Malang.